Avaliação da qualidade microbiológica de carcaças de frango oriundas do abate kosher: influência das etapas de salga e dessalga sobre alguns parâmetros higiênico-sanitários - Izidoro, Thiago Braga [UNESP] (2011)
A food is considered kosher when changes are made in their flowcharts production directed by rules contained in the Torah, the sacred book of the Jewish people. In the case of the broiler ́s slaughter, were inserted in two important steps compared to conventional slaughter, a process of salting, followed by a desalting procedure of carcasses. The aim of this study was to evaluate the microbiological quality of chicken carcasses slaughtered by kosher method, and analyze the influence of specific steps of this kind of slaughter. For that 152 carcasses were analyzed, 38 chickens collected in each of the following moments: before salting (AS) after salting (DS), after desalting (DD) and the final product (FP). It were conducted the following microbiological tests: aerobic mesophilic count, coliform count at 35 ° C, E. coli count, and it was verified the presence of Salmonella spp., Listeria innocua and Listeria monocytogenes. Similarly, another 140 carcasses were collected (35 at each point, as described) to perform the quantification of NaCl. The results show a good microbiological quality of carcasses, not having been a statistically significant influence of salting and desalting steps on microbiological parameters evaluated. It is concluded that the microbiological quality of Kosher carcasses is more due to compliance with the hygiene standards than the above mentioned steps ́insertion.